1996
DOI: 10.1080/10407789608913830
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of Heat Transfer by Rows of Rectangular Impinging Jets

Abstract: The velocity field and heal transfer in rows of rectangular impinging jets have been analyzed from the numerical solution of unsteady Nauier-Stokes and energy equations. Jets emanating axially and radially from rectangular slot nozzles ifeed tubes} have been considered. For the radial jets, the jet exit angle has also been varied. Steady flows have been obtained for Reynolds numbers smaller than a critical value above which periodic flows appear. At a higher Reynolds number than the critical value. the flow be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…The SOJIN is exceptionally beneficial when standard in-line nozzles are required to work closer to the impingement surfaces than their optimal spacing. Jets emanating axially and radially from rectangular slot nozzles (feed tubes) have been considered by Laschefski et al [3]. They found that for densely spaced jets (i.e., for a large relative nozzle area), average heat transfer for the radial jets can be larger than that for axial jets.…”
Section: Introductionmentioning
confidence: 98%
“…The SOJIN is exceptionally beneficial when standard in-line nozzles are required to work closer to the impingement surfaces than their optimal spacing. Jets emanating axially and radially from rectangular slot nozzles (feed tubes) have been considered by Laschefski et al [3]. They found that for densely spaced jets (i.e., for a large relative nozzle area), average heat transfer for the radial jets can be larger than that for axial jets.…”
Section: Introductionmentioning
confidence: 98%
“…The numerical simulation of jet array system in the laminar range is also quite scarce. The numerical simulations of Mikhail et al [7], Seyedein et al [8] and Laschefski et al [9] are related with impingement of rows of laminar slot jets which are all two-dimensional. The present work deals with laminar, three-dimensional, analysis of 3 × 3 square array of confined square air jets impinging on a heated flat surface with spent fluid removal.…”
Section: Introductionmentioning
confidence: 99%
“…Seyedein et al [5] demonstrated a numerical simulation for turbulent flow field and heat transfer of three and five turbulent heated slot jets discharging normally into a confined channel. Laschefski et al [6] numerically analyzed the velocity field and heat transfer in rows of rectangular impinging jets in the transient state. Cziesla et al [7] simulated turbulent flow issuing from a slot jet array using a subgrid stress model.…”
Section: Introductionmentioning
confidence: 99%